2008
DOI: 10.1016/j.memsci.2008.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation and characterisation of biopolymer clusters in a submerged membrane bioreactor

Abstract: A laboratory wastewater treatment membrane bioreactor (MBR) with a submerged hollow-fibre membrane was used to investigate the major foulants in sludge mixtures. Confocal laser scanning microscopy (CLSM) with a triple fluorescent staining protocol, i.e., SYTO9 for microbial cells, ConA-TRITC lectin for polysaccharides and NanoOrange for proteins, was utilised to visualise the fouling materials. A pool of biopolymer clusters (BPC) ranging from 2.5 to 60 μm in size was identified in the liquid phase of the MBR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 35 publications
0
42
0
1
Order By: Relevance
“…In trials with a lab-scale MBR fed on synthetic wastewater, they found a weak correlation between BPC concentration (i.e., c TOC ) and TMP as a function of productivity (permeate volume over membrane surface). The group visualised clusters ranging from 2.5 to 60 m in size [67].…”
Section: Identification Of Foulantsmentioning
confidence: 99%
“…In trials with a lab-scale MBR fed on synthetic wastewater, they found a weak correlation between BPC concentration (i.e., c TOC ) and TMP as a function of productivity (permeate volume over membrane surface). The group visualised clusters ranging from 2.5 to 60 m in size [67].…”
Section: Identification Of Foulantsmentioning
confidence: 99%
“…6a and b shows that MBR-PAC in stages 1-3 suffered slightly from membrane fouling because the polysaccharide did not cause significant effect on the irreversible fouling due to a major portion of them were biodegraded (Taimur Khan et al, 2013). Furthermore, higher protein/polysaccharide ratio indicated higher hydrophobicity of sEPS (Sun et al, 2008) and the affinity between proteins and foulants should generally be greater than that of polysaccharides in relation to their hydrophobicity and surface charge (Taimur Khan et al, 2013). In day 41-50, protein/polysaccharide ratio in MBR-PAC was lower than SMBR.…”
Section: Influences Of Pac On the Characteristics Of Permeationmentioning
confidence: 99%
“…The cake layer and mixed liquor were extracted and analyzed with regard to EPS and SMP based on the methods as demonstrated in our previous study [23]. BPC were obtained by following the method proposed by Sun et al [24]. In this study, the extracted samples were normalized as the sum of proteins (EPS P , SMP P , BPC P ) and polysaccharides (EPS C , SMP C , BPC C ).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…More sludge cake on membrane surface could cause endogenous decay or cell lysis at the bottom layer, which led to release of more EPS P and SMP [40,41]. Furthermore, the continuous accumulation of SMP in the sludge layer generated more BPC on membrane surface, which accelerated the formation and attachment of a sticky and impermeable sludge cake on the membrane surface [7,24]. On contrary, in the MBR-G, Gemfloc Ò addition not only reduced deposition of EPS P by lowering TMP development, but also adsorbed SMP P and SMP C , resulting in less retention of BPC P and BPC C in the sludge cake.…”
mentioning
confidence: 99%